Characterizing and Understanding the Low Back Pain Experience Among Persons with Lower Limb Loss. Issue 5 (9th November 2019) - Butowicz, Courtney M; Silfies, Sheri P; Vendemia, Jennifer; Farrokhi, Shawn; Hendershot, Brad D
Abstract: Objective: This study preliminarily characterizes and compares the impact of lower limb loss and development of chronic low back pain (cLBP) on psychosocial factors, as well as the relationship between these factors and low back pain–related functional disability. Design: Cross-sectional study. Methods: Participants were adults, active duty or retired military, with traumatic lower limb loss with and without chronic low back pain. Psychosocial factors and low back pain–related functional disability were measured using common clinical self-report questionnaires. The presence of psychosocial factors was compared between those with and without cLBP using multivariate analysis of covariance ( P < 0.05), and correlations determined relationships between psychosocial factors and cLBP-related functional disability. Results: There were no statistically significant differences among psychosocial factors between those with vs without cLBP ( F (4, 13) = 0.81, P = 0.54, η 2 = 0.19). Employment status ( ρ = 0.43, P = 0.02), anxiety ( ρ = 0.45, P = 0.04), and kinesiophobia ( ρ = 0.47, P = 0.04) were moderately associated with low back pain–related disability. Conclusions: Psychological (i.e., anxiety) and social (i.e., employment status) factors may influence how persons with traumatic lower limb loss respond to self-reported measures of low back pain–related disability. The findings suggest that the Modified Oswestry Disability Index identifies cLBP-related functional disability in the context of lower limb loss. These results support the interdependence among biological, psychological, and social factors, which should be collectively considered during the development of rehabilitative strategies to treat secondary musculoskeletal conditions within this population.